1982
DOI: 10.1149/1.2124008
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Conductivity in Lanthanum‐Doped Strontium Titanate

Abstract: The electrical conductivity of polycrystalline SrTiO3 doped with 0.1–2 atom percent lanthanum was determined for the oxygen partial pressure range of 100–10−22 atm and temperature range of 850°–1050°C. Two types of charge compensation were observed, electronic and ionic. In the overstoichiometric or ionic compensation range of the oxide, a model involving a shear structure is considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
63
0
2

Year Published

1982
1982
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(74 citation statements)
references
References 6 publications
9
63
0
2
Order By: Relevance
“…Thermopower measurements demonstrate that these materials become n-type in air [21]. However, the understanding of defect chemistry is still inconclusive due to uncertainty concerning the incorporation of donor species (as found for Srl.xLaxTiO 3 materials [20]), or unusual changes in conductivity on changing from reducing to oxidizing conditions. Vernicke [15,16] suggested that slow reequilibration of the main charge carrier concentration on the reoxidation might be slow due to its dependence on the diffusion of vacancies.…”
Section: Proposed Defect Chemistry Model Formentioning
confidence: 99%
See 1 more Smart Citation
“…Thermopower measurements demonstrate that these materials become n-type in air [21]. However, the understanding of defect chemistry is still inconclusive due to uncertainty concerning the incorporation of donor species (as found for Srl.xLaxTiO 3 materials [20]), or unusual changes in conductivity on changing from reducing to oxidizing conditions. Vernicke [15,16] suggested that slow reequilibration of the main charge carrier concentration on the reoxidation might be slow due to its dependence on the diffusion of vacancies.…”
Section: Proposed Defect Chemistry Model Formentioning
confidence: 99%
“…For example, high temperature volatilization losses of SrO may cause A-site deficiency, and this is probably accounted for by the formation of strontium vacancies and oxygen vacancies. An alternative defect chemistry model is also easily derived on assuming the formation of Schottky defects, and a third hypothesis may be based on assuming segregation of SrO in SrO-rich domains as proposed by the Balachandran and Eror [20]. These authors proposed the formation of layered structures (SrO.nSrTiO3) to accommodate the excess of Sr in SrvxLaxTiO3+~.…”
Section: Introductionmentioning
confidence: 99%
“…Overall electroneutrality of the lattice can be achieved by two different mechanisms, namely, electronic compensation and cation-vacancy compensation. [30][31][32] . As a result, the electrical conductivity of the material is again improved.…”
Section: Introductionmentioning
confidence: 99%
“…(2) . However, there are at least three compensation mechanisms in Ladoped SrTiO 3 , which can also be dependent on the conditions of synthesis, e.g., and temperature [20][21][22] . These are listed as mechanisms (2)- (4) and represent electronic, A-site and B-site vacancies, respectively.…”
Section: Introductionmentioning
confidence: 99%